MULTI-VARIANCE ANALYSIS OF CONTENT MARKETING EFFECTS ON CUSTOMER ENGAGEMENT FROM PT WOW INSTAGRAM HALAL COSMETICS - Noer, Bustanul Arifin; Baraja, Adibah Ali; Wicaksono, Adhika Putra (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
The growth of the global cosmetic industry, including in Indonesia, is supported by technology and internet development, with Instagram content marketing playing a key role in shaping positive brand meaning through customer engagement. This study aims to analyse the role of content marketing aspects on customer engagement. This research used a quantitative approach based on data collected through PT WOW's Instagram posts. MANOVA is used to analyse the influence of several independent variables (content marketing aspects) on more than one dependent variable (number of likes and comments) simultaneously. A total of 1,119 posts were collected over the last 20 months, recorded based on the number of likes, comments, and content. The results of this study state that uploads containing the call to win, the call to act, and the pure question will generate higher customer engagement. Uploads containing benefit-centric content can also create higher customer engagement. Companies can use the managerial implications of this research to select content to be uploaded and aim to attract consumers and increase consumer engagement.JEL: M20, M31.